Movement Notation Revisited: Syntax of the Common Morphokinetic Alphabet (CMA) System - Izquierdo, Conrad; Anguera, M. Teresa (Frontiers in Psychology, 2018)
Advances in the study of non-verbal behavior and communication have generated a need for movement transcription systems capable of incorporating continuous developments in visual and computer technology. Our research team has been working on the construction of a common morphokinetic alphabet for the systematic observation of daily life activities. The project, which was launched several years ago, was designed to create a system for describing and analyzing body motion expression, physical activity, and physical appearance. In this paper, we describe an idiosyncratic application of Noam Chomsky’s phrase marker grammar to the morphokinetic phrase, the objective being to establish the grammatical rules and basic order of the symbol string according to a relational tree formed by the breakdown of the syntactic components identified as structuring the visual description of movement. Criteria for using the CMA as a coding system and a free transcription system are proposed.